Teatro-Educação: Mostra Estudantil de Artes Cênicas em Manaus (1983-1990) - (:unkn) unknown (Universidade Federal do Amazonas, 2020)
This dissertation is a result of research of theater experiences in Manaus city, lived by basic education students in 1980s. Research was delimited in period from 1983 to 1990, a period which was developed by SEDUC / AM, through from defunct Cultural Affairs Coordination - CAC, the project "Arts Center in Schools" which had as one of its actions, the annual holding of "Student Exhibition of scenics Arts". Therefore, the main focus of this research was investigate the theatrical actions developed through the "Student Exhibition of Scenics Arts" and their contributions to funding of theatrical artistic production in Manaus public schools. Specifically, was made a mapping of the actions taken in the eight editions of "Student Exhibition of Scenics Arts" in Manaus, in a historical, political and cultura contextl of 1980s, and through the narratives of the subjects involved in the coordination and realization of this action, we seek to know their perceptions regarding the experience with student theater in the proposed period, your limits and possibilities, as well as the reasons that led to the non-continuity of the project. Methodologically, a qualitative approach was used as a reference, through bibliographic and documentary research, and semi-structured interviews with research subjects. The mapping evidenced that was participation of schools from different regions of Manaus city with constituted student theater groups, and a significant number of theatrical performances presented by basic education students, both in the form of physical theater, as well as puppet theater. From the analysis of the subjects' narratives, was evidenced that the experiences lived by had different impacts in their perception, with recognition that project was an important action in theater-education area, without let to point the difficulties and possibilities of realization. Considering analyzes realized, was concluded that student theater has a significant place in the context of theater history in Manaus city in 1980s, and speeches of the protagonists of this action showed that some of them defined their professional trajectories based on that experience, in other words, the theater guided their professional direction, which means that the art development, and in a specific way theater in schools, is a relevant action in the Education Process.
Keywords: Educação básica; Artes Cênicas; Artes cênicas e crianças; Teatro estudantil; Teatro - Manaus; CIÊNCIAS HUMANAS; Ensino de Arte; Teatro-educação; Teatro estudantil; Anos oitenta; Manaus